Phlaeopterus Motschulsky, 1853 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini)—a new genus for the Palaearctic: new combination - Shavrin, Alexey V.; Mullen, Logan (Zootaxa, 2015)
The genus Phlaeopterus Motschulsky, 1853, which was previously known only from North America, is recorded for the Palaearctic fauna for the first time: P. czerskyi (Shavrin, 2001) comb. nov. (East Siberia: Khamar-Daban Mts.) is transferred from the genus Lesteva Latreille, 1797, redescribed, and illustrated.